2018
DOI: 10.1111/jcmm.13921
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cellular stress is essential for Fibroblast growth factor 1 treatment for diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is one of general and common complication of diabetes, which severely affects the physical and mental health of diabetic patients. Fibroblast growth factor 1 (FGF1), an effective control agent of blood glucose, plays an effective treatment role on diabetes‐induced renal injury. But the specific molecule mechanism underlying it is still unclear. Since induction of cellular stress is the main and common mechanism of diabetes‐induced complication, we hypothesized that reduction of cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
(85 reference statements)
1
17
0
Order By: Relevance
“…The db/db mice were divided into two groups and were intraperitoneally (i.p.) injected either with FGF1 (Guang et al, 2018) (0.5 mg/kg body weight, n = 8) or physiologic saline (n = 8) every other day for 4 weeks (Wu et al, 2018). After 4 weeks, body weights were measured.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…The db/db mice were divided into two groups and were intraperitoneally (i.p.) injected either with FGF1 (Guang et al, 2018) (0.5 mg/kg body weight, n = 8) or physiologic saline (n = 8) every other day for 4 weeks (Wu et al, 2018). After 4 weeks, body weights were measured.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Hyperglycemia with resulting elevated cellular stress is the major mediator of diabetes-associated onset of complications ( Wu et al, 2015 , 2018 ). Multiple studies have shown that the induction of ER stress is responsible for the pathogenetic progression of diabetes-associated neuropathy ( Lupachyk et al, 2013 ; Zhang et al, 2013 ; Wu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a critical transcription factor to maintain redox homeostasis and regulates the expression of antioxidative stress genes including NQO1 and SODs (Dodson et al, 2019). It has been reported that hyperglycemia can induce oxidative stress and increase kidney injure via Nrf2 signaling (Wu et al, 2018). However, interestingly, our results show that bFGF treatment corrected the decreased levels of Nrf2, NQO1, and SOD2 in the kidney of db/db mice.…”
mentioning
confidence: 44%